Extracellular Na+ levels regulate formation and activity of the NaX/alpha1-Na+/K+-ATPase complex in neuronal cells - Berret, Emmanuelle; Smith, Pascal Y.; Henry, Mélaine; Soulet, Denis; Hébert, Sébastien S.; Toth, Katalin; Mouginot, Didier; Drolet, Guy (Frontiers in Cellular Neuroscience, 2014)
MnPO neurons play a critical role in hydromineral homeostasis regulation by acting as sensors of extracellular sodium concentration ([Na+]out). The mechanism underlying Na+-sensing involves Na+-flow through the NaX channel, directly regulated by the Na+/K+-ATPase α1-isoform which controls Na+-influx by modulating channel permeability. Together, these two partners form a complex involved in the regulation of intracellular sodium ([Na+]in). Here we aim to determine whether environmental changes in Na+ could actively modulate the NaX/Na+/K+-ATPase complex activity. We investigated the complex activity using patch-clamp recordings from rat MnPO neurons and Neuro2a cells. When the rats were fed with a high-salt-diet, or the [Na+] in the culture medium was increased, the activity of the complex was up-regulated. In contrast, drop in environmental [Na+] decreased the activity of the complex. Interestingly under hypernatremic condition, the colocalization rate and protein level of both partners were up-regulated. Under hyponatremic condition, only NaX protein expression was increased and the level of NaX/Na+/K+-ATPase remained unaltered. This unbalance between NaX and Na+/K+-ATPase pump proportion would induce a bigger portion of Na+/K+-ATPase-control-free NaX channel. Thus we suggest that hypernatremic environment increases NaX/Na+/K+-ATPase α1-isoform activity by increasing the number of both partners and their colocalization rate, whereas hyponatremic environment down-regulates complex activity via a decrease in the relative number of NaX channels controlled by the pump.